Improving Competence and Entrepreneurship through Skills in Using Total Station in Vocational High School: Peningkatan Kompetensi dan Wirausaha Melalui Keterampilan Menggunakan Total Station Sekolah Menengah Kejuruan - Taufiq Natsir; Anas Arfandi; Dwi Wahyuni Aprianti; Raeny Tenriola Idrus (PT. Lontara Digitech Indonesia, 2024)
This study aims to improve students' competence and entrepreneurship through skills training on the use of Total Station at SMKN 5 Majene. Despite adequate school facilities, the curriculum related to surveying technology, especially the use of Total Station, is still underemphasized, even though this tool is standard in modern construction projects. This program conducted training and workshops involving lecturers who are mapping survey experts. In addition, this program also equips students with entrepreneurial knowledge, opens up career opportunities in the surveying and mapping sector, and increases the competitiveness of graduates in the work industry. The methods used include practical training, ongoing coaching, and comprehensive evaluation to ensure objectives are achieved. The results obtained are that the participants (students) of SMKN 5 Majene have the knowledge and skills in operating a Total Station and have entrepreneurial knowledge who are ready to work and able to utilize their technical skills in the world of work in the field of construction and surveying, which is also expected to contribute to the development of the local economy. Abstrak Penelitian ini bertujuan untuk meningkatkan kompetensi dan kewirausahaan siswa melalui pelatihan keterampilan penggunaan Total Station di SMKN 5 Majene. Meskipun fasilitas sekolah memadai, kurikulum terkait teknologi survei, khususnya penggunaan Total Station, masih kurang ditekankan, padahal alat ini menjadi standar dalam proyek konstruksi modern. Program ini melaksanakan pelatihan dan workshop yang melibatkan para dosen pengabdi ahli survei pemetaan. Selain itu, program ini juga membekali siswa dengan pengetahuan kewirausahaan, membuka peluang karir di sektor survei dan pemetaan, serta meningkatkan daya saing lulusan di industri kerja. Metode yang digunakan mencakup pelatihan praktis, pembinaan berkelanjutan, dan evaluasi komprehensif untuk memastikan tujuan tercapai. Hasil yang diperoleh adalah para peserta (siswa) SMKN 5 Majene memiliki pengetahuan dan keterampilan dalam mengoperasikan Total Station serta telah memiliki pengetahuan kewirausahaan yang siap bekerja dan mampu memanfaatkan keterampilan teknisnya dalam dunia kerja di bidang konstruksi dan survei, yang juga diharapkan dapat berkontribusi pada pengembangan ekonomi lokal.